2019
DOI: 10.3390/ma12091402
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Interfacial Interaction Performance of Branched Bonding Agents and CL-20

Abstract: Adding bonding agents to the formulation is an effective way to solve the dewetting of 2,4,6,8,10,12-hexanitro-2,4,6,8,10,12-hexaazaisowurtzitane (CL-20) in the binder matrix. For the design and selection of the structure of a bonding agent suitable for CL-20, a series of branched polyether bonding agents with terminal groups substituted by cyano, ester and hydroxyl functional groups were employed. Contact angle, Fourier transform infrared spectra (FTIR) and X-ray photoelectron spectroscopy (XPS) measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Also, the peak of the cyano group N of complexes 2 , 3 , and 4 emerges at 399.2, 399.2 and 399.3 eV which are similar to previous research. 48 In Fig. 3(b), the peaks of Co 2p 2/3 and Co 2p 1/2 of complexes 1 , 2 , 3 , and 4 can be fitted to two distinct peaks with binding energies of 794.6/779.4, 794.7/779.5, 794.8/779.6 and 795.0/779.6 eV which are consistent with previous research about the Co III oxidation state.…”
Section: Resultssupporting
confidence: 89%
“…Also, the peak of the cyano group N of complexes 2 , 3 , and 4 emerges at 399.2, 399.2 and 399.3 eV which are similar to previous research. 48 In Fig. 3(b), the peaks of Co 2p 2/3 and Co 2p 1/2 of complexes 1 , 2 , 3 , and 4 can be fitted to two distinct peaks with binding energies of 794.6/779.4, 794.7/779.5, 794.8/779.6 and 795.0/779.6 eV which are consistent with previous research about the Co III oxidation state.…”
Section: Resultssupporting
confidence: 89%
“…The SEM and DMA analyses revealed that CL-20 was well coated, the elongation at break of propellant film was increased by 10%, and the maximum elongations at high temperature and low temperature were increased by 20-30%. Deng et al [74].and Zhao et al [75] respectively compared the binding effects of different hyperbranched polyether bonding agents (BA3, CBPEs, and BPEs) and small molecule bonding agents on solid fillers. The adhesions between BA3/HMX and CBPE-10 and 10/CL-20 reached 67.27 mN•m −1 and 105.37 mN•m −1 , stronger than those between the small molecule bonding agent/solid filler system.…”
Section: Other Types Of Novel Bonding Agentsmentioning
confidence: 99%